The matador - Brosnan, Pierce; Davis, Hope, 1967-; Furst, Bryan; Furst, Sean.; Hall, Philip Baker, 1931-; Kinnear, Greg, 1963-; Shepard, Richard; St. Clair, Beau.; DEJ Productions; Equity Pictures Medienfonds GmbH & Co. KG II.; Furst Films Irish Dreamtime (Firma); Miramax Films; et al. (Del Mar, CA : Weinstein Company : distributed by Genius Products, 2006)
Un tromatamundo asesino a sueldo y un alicaído hombre de negocios se reúnen en un bar en México, en un encuentro que los llevará juntos de una manera inesperada.
DISPONIBLE
Special features: Deleted scenes; feature commentary with director, Richard Shepard; commentary with Pierce Brosnan, Greg Kinnear & Richard Shepard; Making the Matador featurette; The business & the treatment : feature radio programs discuss ’The Matador’; TV commerical; theatrical trailer.
Director of photography, David Tattersall ; art directors, Marcelo Del Rio, Enrique Echeverri ; editor, Carole Kravetz-Aykanian ; music by, Rolfe Kent ; costume designer, Catherine Marie Thomas ; production designer, Robert Pearson.
Pierce Brosnan, Greg Kinnear, Hope Davis, Philip Baker Hall.
MPAA rating: R; for strong sexual content and language.
DVD, region 1, widescreen presentation; Dolby Digital 5.1 surround.
Keywords: Asesinato; Asesinos; Negociantes; Películas cinematográficas